Single-centre retrospective analysis of the best timing for the QTc interval length assessment in neonates - Raffaele Falsaperla; Alessia Marcellino; Jessica Luchetti; Massimo Raponi; Carmelo Pirone; Maria Katia Fares; Flavia Ventriglia; Riccardo Lubrano (BMJ Paediatrics Open)
Objective To evaluate the best timing for ECG screening in order to diagnose long QT syndrome and lower, at the same time, the false positives.Design We retrospectively evaluated the corrected QT (QTc) interval in the clinical reports of the ECG screening performed, as per internal protocol.Setting An outpatient setting in our Unit of Neonatology and Pediatrics, Santa Maria Goretti Hospital in Latina, Italy.Patients We enrolled 3467 healthy neonates between 14 and 30 days of life.Interventions The newborns with abnormal QTc interval were invited to subsequent revaluation every 21 days, until normalisation or necessity to refer to a tertiary paediatric cardiology centre.Main outcome measures Difference in QTc according to patients’ characteristics and number of false positives at second ECG evaluation.Results At first evaluation, 249 (7.2%) newborns had prolonged QTc. We did not find any significant difference in the QTc length according to gestational age (p=0.40) and birth weight (p=0.81). As expected, girls had longer QTc than boys (p=0.01). Only 11 out of 240 (4.6%) and 1 out of 238 infants (0.4%) had persistently prolonged QTc at second and third ECG evaluation, respectively. The QTc decreased significantly at second (p<0.0001) and third evaluation (p=0.0035).Conclusions In our study, we showed that a single screening performed in healthy infants after 60 days of life could reduce the risk of false positives, with a beneficial impact on public national health system and the chance to start early therapy in case of long QT syndrome.